2021
DOI: 10.3390/dairy2040052
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Subclinical Ketosis Detection with Rapid Test Methods for BHBA in Blood in Commercial Dairy Farms

Abstract: This study gives an overview of the performance and accuracy of devices used for the fast measurement of β-hydroxybutyrate (BHBA) in blood for the on-farm indication of subclinical ketosis. Data were collected on ten dairy farms. In each farm, blood samples were taken from ten cows on four test days (2, 4, 9 and 11), resulting in 400 samples. The reference method was the BHBA concentration in blood serum (BHBALAB). Four different devices that measure BHBA in whole blood were tested. The thresholds applied for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Passing‐Bablok regression analysis indicated a negative constant (−0.19) and positive proportional bias (1.46) for the Precision Xtra meter, and a positive constant (0.22) and proportional bias (1.17) for the Taidoc meter in dairy cows 20 . In another study, Jansen et al reported a positive constant (0.092) and proportional bias (0.980) for the TaiDoc BHB‐check meter in dairy cows 5 . The Freestyle Precision meter showed neither a constant nor a proportional bias in that study.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Passing‐Bablok regression analysis indicated a negative constant (−0.19) and positive proportional bias (1.46) for the Precision Xtra meter, and a positive constant (0.22) and proportional bias (1.17) for the Taidoc meter in dairy cows 20 . In another study, Jansen et al reported a positive constant (0.092) and proportional bias (0.980) for the TaiDoc BHB‐check meter in dairy cows 5 . The Freestyle Precision meter showed neither a constant nor a proportional bias in that study.…”
Section: Discussionmentioning
confidence: 96%
“…22 However, when compared with Precision Xceed 9 and WellionVet BELUA meters, 23 the Freestyle Optium Neo H meter consistently overestimated blood β-OHB concentrations in sheep, and the overestimation is more pronounced at higher blood β-OHB concentrations. Although TaiDoc ketone meters have been previously evaluated in dairy cows, 5,20 there have been no studies evaluating TaiDoc ketone meters in sheep. In our study, the TaiDoc-TD4235 meter yielded an extremely high mean bias for blood β-OHB concentrations in sheep compared with previous studies evaluating TaiDoc meters in dairy cows and different ketone meters in sheep.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations